General morphology and ultrastructure of the female reproductive apparatus of Trichomalopsis shirakii crawford (Hymenoptera, Pteromalidae). Issue 7 (6th May 2016) - Mao, Ning; Tang, Pu; Tian, Hong‐Wei; Shi, Min; Chen, Xue‐Xin
ABSTRACT: The morphology and ultrastructure of the female reproductive system were examined for a larval–pupal parasitoid Trichomalopsis shirakii Crawford of Oulema oryzae Kuwayama using light and electron microscopes. The reproductive system includes two ovaries, two pairs of accessory glands, an unbranched venom gland, a large venom reservoir and a Dufour gland. Each ovariole contains follicles and oocytes at different stages of maturation. A fibrous layer covers the surface of mature egg. The accessory glands are made up of a layer of secretory cells surrounded by muscle fibers. In these secretory cells, numerous mitochondria, electron‐dense secretory granules and vesicles filled with dense granular particles are present. These granular particles appear as virus‐like particles (VLPs). The venom gland consists of a single layer of secretory cells which are organelle rich with abundant rough endoplasmic reticulum, mitochondria and vesicular organelles, a layer of duct cells and an inner intima. The reservoir consists of a muscular sheath, epidermal cells with few organelles and an intima layer. The Dufour gland has a relatively large lumen surrounded by a single layer of columnar epithelial cells which are characterized by clusters of smooth endoplasmic reticulum and lipid droplets. Aside from the venom, the fibrous layer coating the egg and the granular particles which may be VLPs have been discovered in our study. They may serve as one of the parasitoid‐associated factors in their host–parasitoid relationship and play a role in host immune suppression. Microsc. Res. Tech. 79:625–636, 2016 . © 2016 Wiley Periodicals, Inc.